Women's experiences of waterbirth compared with conventional uncomplicated births. (December 2019) - Ulfsdottir, Hanna; Saltvedt, Sissel; Georgsson, Susanne
Highlights: The total score of the childbirth experience questionnaire did not differ. Women having a waterbirth ranked their own capacity higher. Women who feel more capable during labour may be less dependent on the midwife. Women having a waterbirth scored less pain and higher of being in control during the 2nd stage of labour. Abstract: Objective: To compare childbirth experiences between women having a waterbirth and women having an uncomplicated conventional birth. Design: A prospective cohort study using the validated Childbirth Experience Questionnaire (CEQ) six weeks postpartum. The 22-item questionnaire assesses four domains of the childbirth experience; Own capacity, Professional support, Perceived safety and Participation. These four domains constituted the main outcome of the study. Further, supplementary questions about the second stage of labour were added to the web-questionnaire. Setting: One city-located hospital in Stockholm and one small-town hospital in Southern Sweden offering waterbirth to low risk women. Participants: 215 women; 99 nulli- and 116 multiparas. 111 gave birth in water and 104 had an uncomplicated conventional birth. Measurements and findings: The total CEQ score did not differ between the groups, while women having a waterbirth scored significantly higher in the domain, "Own capacity" and lower in the domain, "Professional support". Women having a waterbirth rated less pain and higher scores of being in control in the second stage of labour. Key conclusions: A waterbirth seems to empower and enhance women's capacity for those who choose this alternative. Waterbirth can improve their birth experience and can possibly make women less dependent on the midwife. Implications for practice: To provide waterbirth could be a way of empowering women and giving them a positive birth experience.